CONCEPTUALIZATION OF THE DANCE WORK "COMIC SPACE" IN INTERPRETING THE IMAGINATIVE SPACE OF COMIC BOOKS: CONCEPTUALIZATION OF THE DANCE WORK "COMIC SPACE" IN INTERPRETING THE IMAGINATIVE SPACE OF COMIC BOOKS - Palupi, Retno; Yanuartuti, Setyo (Solah, 2025)
The dance work titled Comic Space is inspired by the imaginative space found in comic books. The choreographer explores several visual elements commonly found in comics such as panels, gutters, illustrations, speech balloons, and sound effects. These elements form a compelling two- dimensional space that can be utilized as material to create artistic dance movements. One of the key concepts highlighted is closure, the ability to interpret comic stories from separate images. This idea is applied to choreography by creating an illusion of transition between movements and assembling fragmented, seemingly disconnected movement pieces that, when observed as a whole, convey meaning. This is manifested through body gestures that may appear disjointed individually but form a coherent message when viewed collectively. The creation process follows Jacqueline Smith's Construction Method I, which includes stages such as finding inspiration, determining the type of dance, choosing the presentation mode, exploring movement, evaluation, and refinement. This work is categorized as pure dance, which emphasizes the beauty of movement rather than storytelling. The resulting performance presents contemporary dance that visualizes the world of comics through movement. The choreography emphasizes fast, staccato movements, with a characteristic black and white tone reminiscent of comics. This work aims to inspire further development in contemporary dance creation that blends visual arts with performing arts.